PENINGKATAN KETERAMPILAN PROSES SAINS SISWA SMA DENGAN MODEL PEMBELAJARAN PREDICT-OBSERVEÂ¬-EXPLAIN MATERI HIDROLISIS GARAM - Murezhawati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research is to improve science process skill of grade XI student of SMA Muhammadiyah 2 Pontianak in salt hydrolysis material by using Predict-Observe-Explain (POE) model. The research method used is Class Action Research. The subjects of this study were 31 students of class XI IPA. The research instrument of this is the lesson plan research, student worksheet, and skill observation sheet using tools and materials. The results of the study in first cycle showed the skills of predicting, observing, tabulating, explaining and concluding respectively that is 39%, 97%, 100%, 35% and 48%. In the second cycle there is an increase in the skill of predicting, observing, tabulating, explaining and concluding respectively that is 100%, 100%, 100%, 96% and 61%. It can be concluded that the use of the Predict-Observe-Explain (POE) learning model can improve the science-grade students' skill of class XI IPA SMA Muhammadiyah 2 Pontianak on salt hydrolysis material.Keywords: POE, Skills Process Science, Hydrolysis Salt